Identification of the relationships between critical success factors, barriers and practices for lean implementation in a small company - Pereira, Laís; Tortorella, Guilherme (Brazilian Journal of Operations & Production Management, 2018)
This article aims to identify how the critical success factors (CSF), barriers and practices for lean manufacturing (LM) implementation in a small company are related. For this, the CSF, barriers and practices of LM related to small companies were initially consolidated from a literature review. Through semi-structured interviews and focus groups with the leaders of a small electronics manufacturing company in lean implementation, the relationships were evaluated and ranked through the incorporation of a multi-criteria analysis tool. The integration of a multi-criteria analysis tool into qualitative research methods (focused groups, semi-structured interviews and participatory observation) allowed quantifying these relationships in order to identify convergent efforts for a successful LM implementation. Existing frameworks for lean implementation are targeted at larger companies, disregarding the specific small company context. This study provides a guide to assist LM implementation in small manufacturing companies. Furthermore, the greater understanding of these relationships enables managers to anticipate potential problems, allowing a more successful implementation.